Perlindungan Hukum Terhadap Anak Sebagai Korban Kekerasan Dalam Rumah Tangga - Devi Ariani; Aryono Aryono; Muhammad Habib; Evi Elisanti (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This study aims to determine 1) the legal protection of children as victims of domestic violence. 2) the obstacles faced and alternative solutions provided to children as victims of domestic violence. This research method uses a normative-empirical legal approach with a prescriptive research type, focusing on literature studies. The data used are primary data through interviews and secondary data sourced from primary, secondary, and tertiary legal materials. The data collection technique is carried out through literature studies. The data analysis technique is descriptive qualitative with data reduction, data presentation, and drawing conclusions. The results of the study indicate that the study shows that Law Number 35 of 2014 provides legal protection for child victims of domestic violence and guarantees the fulfillment of children's rights so that they can live, grow, develop, and participate optimally in accordance with human dignity and dignity, and receive protection from violence and discrimination, for the realization of quality, noble, and prosperous Indonesian children. Obstacles include lack of human resources, inadequate facilities, difficulty in obtaining information from victims because they are still afraid, ashamed, and traumatized, and lack of public awareness regarding domestic violence against children. Alternative solutions include prevention through education of parents and the community. Awareness campaigns with public education, strengthening the role of schools, legal protection by strengthening regulations to protect children from violence. Economic empowerment programs for victim families. Handling cases of violence through reporting and early intervention, psychological assistance, enforcement of child protection laws, rehabilitation. Long-term recovery and support through psychosocial guidance, access to education and health, adoption and foster care programs. Prevention and handling of child violence requires cooperation from all parties, including families, schools, communities, and the government so that children can grow up in a safe and healthy environment.